Nitrogen factor of common carp Cyprinus carpio fillets with and without skin - Alena Honzlova (Nature Portfolio, 2021)
Abstract Consumer protection against food adulteration and misleading labelling is integrated into EU legislation, but accurate analysis of the meat content of farmed freshwater fish products is not possible because of the lack of established nitrogen factors for farmed common carp. The aim of this study was to determine nitrogen factors for farmed common carp Cyprinus carpio. Seven-hundred samples collected in 2018–2019 in three harvest seasons (March/April, Jun/July, and October/November) at seven locations in the Czech Republic were analysed for nitrogen, dry matter, protein, ash, and fat content according to standard ISO methods. The recommended nitrogen factor for fat-free common carp fillet with skin is 3.04 ± 0.13 and, for fillet without skin, 2.95 ± 0.12. Availability of nitrogen factors for common carp can help ensure that consumers are purchasing correctly labelled products.